Adult groin hernias: acute and elective. Issue 5 (May 2018) - McDonnell, Declan; Wakefield, Christian
Abstract: Groin hernias are a common general surgical condition and inguinal hernias will affect over a quarter of the male population in their lifetime. As a consequence, inguinal hernia repair remains one of the most frequently performed general surgical procedures carried out in the UK, at a cost of £100 million to the National Health Service per annum. Although hernia-related complications are relatively rare, they may be catastrophic and repair is recommended because of the potential functional consequences for the patient and the impact on quality of life. These issues need thorough consideration when deciding upon treatment, particularly in reference to the suitability of the patient, the nature of the hernia to be repaired and the type of surgical approach to be utilized. As with many other areas in medicine, improved outcomes in hernia surgery are achieved by experienced high-volume operators with a specialist interest in the condition. This is particularly the case with laparoscopic hernia surgery, which when introduced was associated with significant complications, and continues to have a steep learning curve. In light of the prevalence of the condition and the potential morbidity associated with hernia treatment, these factors have important global socio-economic implications.